Precise orbit determination and point positioning using GPS, Glonass, Galileo and BeiDou - Tegedor J.; Øvstedal O.; Vigen E. (Journal of Geodetic Science)
State of the art Precise Point Positioning (PPP) is currently based on dual-frequency processing of GPS and Glonass navigation systems. The International GNSS Service (IGS) is routinely providing the most accurate orbit and clock products for these constellations, allowing point positioning at centimeter-level accuracy. At the same time, the GNSS landscape is evolving rapidly, with the deployment of new constellations, such as Galileo and BeiDou. The BeiDou constellation currently consists of 14 operational satellites, and the 4 Galileo In-Orbit Validation (IOV) satellites are transmitting initial Galileo signals. This paper focuses on the integration of Galileo and BeiDou in PPP, together with GPS and Glonass. Satellite orbits and clocks for all constellations are generated using a network adjustment with observation data collected by the IGS Multi-GNSS Experiment (MGEX), as well as from Fugro proprietary reference station network. The orbit processing strategy is described, and orbit accuracy for Galileo and BeiDou is assessed via orbit overlaps, for different arc lengths. Kinematic post-processed multi-GNSS positioning results are presented. The benefits of multiconstellation PPP are discussed in terms of enhanced availability and positioning accuracy.